2015
DOI: 10.1007/s40119-015-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Routine Invasive Versus Selective Invasive Therapy in Women with Non-ST-Elevation Acute Coronary Syndrome

Abstract: IntroductionPrior studies suggested that a routine invasive approach in the management of non-ST-elevation acute coronary syndrome (NSTE-ACS) is beneficial in men, but the data are less conclusive in women. One study conducted exclusively in women found that routine invasive therapy was associated with a markedly increased risk of major bleeding. This pilot randomized controlled trial compared the safety of a routine invasive versus a selective invasive strategy among women.MethodsWomen with NSTE-ACS and an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The composite of all‐cause mortality or MI was reported by 10 trials . Compared with a selective invasive strategy, a routine invasive strategy was associated with a significant reduction in the composite of all‐cause mortality or MI (15.5% vs. 17.5%; OR: 0.86, 95% CI: 0.77‐0.96, P = 0.009) at a mean of 39 ± 12 months (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The composite of all‐cause mortality or MI was reported by 10 trials . Compared with a selective invasive strategy, a routine invasive strategy was associated with a significant reduction in the composite of all‐cause mortality or MI (15.5% vs. 17.5%; OR: 0.86, 95% CI: 0.77‐0.96, P = 0.009) at a mean of 39 ± 12 months (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1). A total of 12 trials with 9,650 patients were included in the final analysis . Four of the included studies reported outcomes at both the intermediate and long‐term follow‐up periods .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In our study, with an OR of 0.55 and an event rate of 3.8% in the control arm, we estimated that 2635 women would be needed in each group to achieve 80% power for in-hospital mortality, which is almost double the number of women enrolled in that patient-level analysis. 7 To date, only 2 randomized trials have attempted to compare both strategies exclusively in women 9,14 ; one of these trials was relatively small (ie, enrolled only 40 women) and showed no difference in clinical outcomes. 14 In the Organization to Assess Strategies in Acute Ischemic Syndromes 5 substudy in women, an early invasive strategy was associated with a higher risk of mortality at 1 year, which could have been driven by the increased risk of major bleeding at 30 days.…”
Section: Discussionmentioning
confidence: 99%